2020
DOI: 10.1029/2020pa003890
|View full text |Cite
|
Sign up to set email alerts
|

Compound‐Specific Radiocarbon Analysis of (Sub‐)Antarctic Coastal Marine Sediments—Potential and Challenges for Chronologies

Abstract: In Antarctic and Subantarctic environments, 14 C-based age determination is often challenging due to unknown reservoir effects, low organic carbon contents of sediments, and high contributions of petrogenic (14 C-free) carbon in ice marginal settings. In this study, we evaluate possible benefits and challenges of compound-specific radiocarbon analysis (CSRA) as a tool for age determination of marine Antarctic and Subantarctic sediment sequences. We present a comprehensive data set of 14 C ages obtained on bulk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 73 publications
0
17
0
Order By: Relevance
“…A proxy group which is especially prone to such lag times is terrestrial organic biomarkers, e.g., long-chain n-alkanes derived from leafs and roots of terrestrial plants, which are frequently used as hydroclimatic indicators (Eglinton and Hamilton 1967;Castañeda and Schouten 2011). This is mainly because of significant residence time in soils due to high recalcitrance of compounds, their transport via rivers, as well as mixing processes, resuspension, and redistribution of material from floodplains from which it was reworked after a long accumulation time (Pearson and Eglinton 2000;Ohkouchi et al 2003;Smittenberg et al 2004;Mollenhauer et al 2005;Mollenhauer and Eglinton 2007;Eglinton and Eglinton 2008;Vonk et al 2014;Winterfeld et al 2018;Berg et al 2020;Bliedtner et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A proxy group which is especially prone to such lag times is terrestrial organic biomarkers, e.g., long-chain n-alkanes derived from leafs and roots of terrestrial plants, which are frequently used as hydroclimatic indicators (Eglinton and Hamilton 1967;Castañeda and Schouten 2011). This is mainly because of significant residence time in soils due to high recalcitrance of compounds, their transport via rivers, as well as mixing processes, resuspension, and redistribution of material from floodplains from which it was reworked after a long accumulation time (Pearson and Eglinton 2000;Ohkouchi et al 2003;Smittenberg et al 2004;Mollenhauer et al 2005;Mollenhauer and Eglinton 2007;Eglinton and Eglinton 2008;Vonk et al 2014;Winterfeld et al 2018;Berg et al 2020;Bliedtner et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…2). A more depleted Δ 14 C value, thus, absence of bomb-14 C, for the lower limit of the terrigenous endmember is supported by a Δ 14 C value of À116‰ determined for C 26:0 fatty acid from a surface sediment sample in Little Jason Lagoon (Co1305), which confirms the mixed composition of terrigenous OM (Berg et al 2020) and is within the range of Δ 14 C values found in surface soils (Shi et al 2020). For the mixing models we, thus, use a Δ 14 C terr of À16 AE 138‰.…”
Section: Biomarker Sourcesmentioning
confidence: 61%
“…3). Yet, a predominantly aquatic origin of low‐molecular‐weight fatty acids in the marine sediments of Cumberland Bay and Little Jason Lagoon is supported by their compound‐specific 14 C ages in comparison to those of the concurrent high‐molecular‐weight fatty acids (Berg et al 2020). However, we cannot exclude low‐molecular‐weight fatty acid contributions from plants/peat a priori.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations